THE EFFECTS OF PANORAMIC RADIOGRAPHY ONGINGIVAL CREVICULAR FLUIDVOLUME IN WISTAR RATS WITH PERIODONTITIS - Ramadhanty, Aina; Aspriyanto, Didit; Oktiani, Beta Widya (Dentino : Jurnal Kedokteran Gigi, 2021)
ABSTRACTBackground: Panoramic radiography is one of the most commonly used radiographic diagnostic tools. Panoramic radiography exposure can increase the GCF flow because of increasing vascular permeability.GCF flow can also increase in periodontitis conditions. Objective: The purpose of this study was to analyze the effects of 1, 2, and 3 times exposure of panoramic radiography to the volume of GCF in wistar rats with periodontitis. Method: This research was true experimental with post test onlycontrol group design. Thesampling technique used simple random samplingthat obtained 25 wistar rats comprising of 5 wistars from each group in which the GCF samples of each group was collected from. Results: The average number of GCF inhealthy rats groupthat was not exposed to panoramic radiographywas 0.114 µL, the periodontitis rats group that was not exposed to panoramic radiography was 0.246 µL, the periodontitis rats group that was exposed1 time was 0.286 µL, the group of periodontitis rats exposed 2 times was 0.294 µL, and periodontitis group of rats exposed 3 times was 0.374 µL. The results of the One-Way Anova and Post Hoc Bonferroni tests stated that there is a significant increase in the volume of GCF between the control group and all other treatment groups, as well as between the non-exposed periodontitis group and the periodontitis group with 3 times exposure. Conclusion: Panoramic radiography can causeincrease the volume of GCF in wistar rats with periodontitis. Keywords: Gingival Crevicular Fluid,panoramic, periodontitis, wistar rats